Functions of the integrated computer system of Ministry of the Treasury within the scope of exercising the owner’s supervision - Żabski, Łukasz (Business Informatics, 2014)
The purpose of the paper is to present functions of the integrated computer system of MST within the scope of exercising the owner’s supervision. In achieving the objective there has been used the method of analysis of literature on the exercising the owner’s supervision in the business entities with the share of the State Treasury (ST) and the method of analysis of the documents of MST and the Supreme Audit Office. The first part of the paper presents the essence of owner’s supervision system over companies with the share of the State Treasury. It is also characterized as Integrated Computer System (ICS) which was purchased in 1999 and implemented in MST. The next part indicates the features and capabilities of the subsystem modules „Monitoring of the Owner’s Transformations and Supervision over the Property of ST”. Moreover, the module ”Generator of Quarterly Questionnaires” is evaluated based on own studies paying special attention to supporting the internal mechanism of the owner’s supervision
Informatyka Ekonomiczna = Business Informatics, 2014, Nr 2 (32), s. 235-248
Keywords: owner’s supervision; integrated computer system; Ministry of the State Treasury; nadzór właścicielski; zintegrowany system informatyczny (ZSI); Ministerstwo Skarbu Państwa